New Ion Selective Electrodes for Analysis of Metformin Based on Molecularly Imprinted Polymers - Mohammed, Nabeel; Al-Bayati, Yehya (Al-Nahrain Journal of Science, 2024)
Metformin (MEF) imprinted polymer liquid electrodes are created using a precipitation polymerization process. The MEF served as a template for the creation of molecularly imprinted (MIP) materials using benzoyl peroxide (BPO) as an initiator, allyl methacrylate (AMA) crosslinkers, and glycidyl methacrylate (GMA) as a monomer. Utilizing Di-octyl-phthalate (DOPH) and di-butyl phthalate (DBPH) as plasticizers in a PVC matrix, the molecularly imprinted membranes are created. The reaction time is approximately 50 seconds, and the limits of detection for liquid electrodes, as determined by the calibration curves, are 55.6 to 58.4 mV/decade at 5×10-5 M and 8×10-5 M respectively. The liquid electrodes demonstrated good selectivity over a variety of species and a consistent reaction when filled with a typical 0.1 M drug solution across the pH range of 1 to 11. Modern electrodes can detect MEF without the need for time-consuming pre-treatment procedures in pharmaceutical samples.